Optimal control method determination of the practice - Луценко, Игорь Анатольевич (Technology audit and production reserves, 2013)
The use of the direct method of determining the optimization parameters in automatic control systems is considered, and some results of researches in this area are given in the paper. The main objective of the study is to obtain an information base for the evaluation of research results in the field of optimal control and the possibility of objective selection of optimization criteria, relying on actual data of researches. The results of practical application of the theoretical developments in the field of optimal control are very modest. It is largely connected with the inability to verify in practice the results of using this or that theory, related to the implementation of optimal control principles. The method for objective evaluation of theoretical and practical works in the field of optimal control is considered in the paper. This method allows assessing the appropriateness of the selection of optimal control criterion, which should bring control to the mode, providing the maximization of the added value. The research results can be used by experts, designing control systems, as well as researchers, developing the optimal control criteria. In fact, the proposed approach allows ensuring an objective assessment of scientific and practical solutions in the field of optimal control in manufacturing processes of product conversion, transport systems and inventory-control systems.